Evaluation of the energy efficiency of a large wastewater treatment plant in Italy. (1st January 2016) - Panepinto, Deborah; Fiore, Silvia; Zappone, Mariantonia; Genon, Giuseppe; Meucci, Lorenza
Highlights: The full scale energy utilization in WWTP has been defined. The energy efficiency of the plant corresponds to the best performances of large scale. The thermal balance from sludge digestion and drying has been considered. Improvement in energy efficiency had proposed. Abstract: Energy consumption represents a significant part of the operative costs of a wastewater treatment plant but, with a correct design and a careful management model, there are important possibilities for its limitation. The proposed research presents a multi-step methodology for the evaluation of the energetic aspects of wastewater treatment, which was implemented on the largest facility in Italy (2.7 M population equivalents as organic load), managed by Società Metropolitana Acque Torino (SMAT). The study initially took into account each phase of the process scheme, in order to obtain specific electricity consumption values for all the electro-mechanic devices. Data from tele-control system and direct measurements in field have both been acquired. The total electric energy demand of the plant was evaluated (66.78 GW h/y, about 50% from aeration in oxidation tanks). In account of large contribution the energy efficiency of the blowers was verified with positive results. Four specific energy consumption indexes were considered to carry out a critical analysis of SMAT wastewater treatment plant with other facilities performing biological oxidation processes and of a different order of magnitude about design capacity, and congruent values were obtained. The considered indexes related the electric energy demand to the equivalent population, to the volume of treated water and to the amount of removed COD and total Nitrogen. Furthermore the thermal energy demand of the plant was estimated (49.15 GW h/y, more than 93% from sludge line). An energy balance for the whole plant was finally evaluated, and some energy optimization solutions to decrease the corresponding costs were suggested.